Fibrinogen for the prediction of severe maternal complications in placental abruption with fetal death after 24 weeks of gestation. Issue 3 (3rd September 2022) - Atallah, Anthony; Piccin, Gaelle; Dubernard, Gil; Abdul‐Hay, Marie Jo; Cortet, Marion; Huissoud, Cyril
Abstract: Objective: To assess the correlation between standard laboratory indicators at admission and severe maternal complications due to placental abruption (PA) with intrauterine fetal death (IUFD) after 24 weeks. Methods: Retrospective study in three French tertiary referral hospitals. Correlation of laboratory indicators at admission (platelet count, prothrombin, activated partial thromboplastin time, fibrinogen) and severe maternal complications (massive transfusion, multiple organ failure, hysterectomy, or maternal deaths) in patients with PA and IUFD. Results: Over 12 years, we identified 27/344 (7.8%) pregnant women presenting PA with IUFD. No patient had coagulopathy at admission. Fifteen individuals (55.5%) underwent delivery by cesarean section before or during labor. Fifteen individuals (55.5%) presented severe complications, and 17/27 (63%) lost more than 1 L of blood during delivery. Fibrinogen level was shown to be the laboratory indicator most correlated with severe complications ( r = −0.52, P = 0.01). The receiver operating characteristic curve of fibrinogen less than 1.9 g/L in the prediction of severe complications (area under the curve = 0.80, 95% confidence interval [CI] 0.54–0.97) showed both a sensitivity and specificity of 83% (95% CI 54%–96%). Conclusions: In cases of IUFD with PA, fibrinogen levels at admission had a prognostic value for the prediction of severe maternal complications. Synopsis: In fetal death with placental abruption, maternal fibrinogen levels at admission <1.9 g/L have a prognostic value for the prediction of severe maternal complications.